Phylogeography of the subgenus Transphlebotomus Artemiev with description of two new species, Phlebotomus anatolicus n. sp. and Phlebotomus killicki n. sp - Kasap, Ozge Erisoz; Dvorak, Vit; Depaquit, Jérôme; Alten, Bulent; Votypka, Jan; Volf, Petr (Infection, genetics and evolution, 2015)
The subgenus Transphlebotomus comprises sand fly species with distribution markedly restricted to the Mediterranean basin and suspected of Leishmania transmission. Only three species, Phlebotomus mascittii, Phlebotomus canaaniticus and Phlebotomus economidesi, have been described up to the present. Due to their similar morphology, proper identification remains difficult and relies mainly on molecular markers. We studied sand fly species of this subgenus from Crete and south-western coast of Anatolia. Based on the sequencing analysis of mitochondrial genes (cytochrome b, NADH dehydrogenase subunit 4, cytochrome oxidase I), two new Transphlebotomus species were identified and subsequently distinguished also by morphological characters: Phlebotomus anatolicus n. sp. and Phlebotomus killicki n. sp. Moreover, Ph. economidesi, previously only recorded from Cyprus, was found in Turkey sympatrically with these two new species. Based on the divergence time estimates, the first split has occurred in the subgenus Transphlebotomus ∼10 million years ago and the paleogeographic events took place around the Aegean and Mediterranean regions were suggested as the main drivers of the diversification of the subgenus. Our findings indicate that for Transphlebotomus species, morphological identification should be confirmed by molecular approaches, especially for investigations concerning their possible vectorial role in Leishmania transmission.
Keywords: Cytochromes b; Evropa; druhová specificita; Divergence; Europe; Animals; Transphlebotomus; Phylogeography; vznik druhů (genetika); Humans; Species Specificity; Multilocus Sequence Typing; Phlebotomus killicki n. sp.; Insect Proteins; fylogeografie; hmyzí proteiny; multilokusová sekvenční typizace; Leishmaniasis; leishmanióza; Biogeography; hmyz - vektory; Genetic Speciation; zvířata; fylogeneze; Insect Vectors; Phlebotomus; Mitochondrial DNA; Ph. anatolicus n. sp.; cytochromy b; lidé; Phylogeny